A Ca. 2.8‐Ga Plume‐Induced Intraoceanic Arc System in the Eastern North China Craton. Issue 5 (22nd May 2019) - Gao, Lei; Liu, Shuwen; Zhang, Bo; Sun, Guozheng; Hu, Yalu; Guo, Rongrong
Abstract: The conversion of Archean tectonic regimes from mantle plume to plate tectonic and the mechanism of subduction initiation are two crucial issues in the current Earth sciences. A typical komatiite‐tholeiite sequence consisting of ~2, 850–2, 800‐Ma komatiites and ~2, 780–2, 710‐Ma basaltic and andesitic to dacitic volcanic rocks is well preserved in the Archean Western Shandong terrane of the eastern North China Craton. These volcanic rocks were derived from the partial melting of a depleted mantle source with subsequent fractional crystallization, a metasomatized subarc mantle wedge, and a descending oceanic slab. Structural and kinematic observations suggest that the Qixingtai‐Yanlinguan‐Panchegou granite‐greenstone belt experienced ~2.85–2.80‐Ga extensional deformation (D1 ) by upwelling of a mantle plume and NE‐SW‐oriented shortening (D2 ) during ~2.78–2.71 Ga. The petrogenesis of the Mesoarchean to early Neoarchean metamorphosed volcanic rock series and regional deformation indicate that a plume‐induced self‐sustaining intraoceanic arc system with SW‐dipping subduction polarity operated ~2.8 Ga, followed by the evolution from initial to mature subduction. An increasing pull caused by the descending slab generated gravitational instability in the surrounding oceanic lithosphere and formation of a new initial subduction zone adjacent to the preexisting arc system. Similar to the process in the Western Shandong terrane, plume activity generally culminated in subduction events in many other Archean greenstone belts, revealing that plume‐arc interaction may have been a crucial mechanism for global Archean tectonic regime conversion from mantle plume to initial plate subduction in the crust of the early Earth. Key Points: Upwelling of a mantle plume caused ~2.85–2.80‐Ga extensional deformation (D1 ) in the WST Ca. 2.78–2.71‐Ga shortening (D2 ) that induced by intraoceanic subduction culminated the D1 deformation Plume‐induced subduction initiation was a crucial mechanism for global Archean tectonic regime conversion